A leitura literária como experiência performática: estudo das práticas leitoras de professores de língua inglesa - Dall Agnol, Samira (My University, 2021)
This thesis analyzes the literary reading practices of English language teachers in order to understand them as performance experiences. The theoretical foundation starts with a comprehension of reading, grounded on Leffa (1996), Kleiman (1995), Solé (1998), Silva (1997), Jouve (2002), Terra (2014), Britto (2015), Eco (1991) and Petit (2009; 2013; 2019). It also features aspects of Reception Aesthetics, based on the contributions of Jauss (1979; 1994) and Iser (1979; 1999); as well as the Cultural Industry, with the discussions proposed mostly by Adorno (1986; 2010). Elements of the Sociology of Reading were added to the thesis with the contribution of Bourdieu (1982; 1996) and Chartier (1994; 2001a, 2001b) and, through the Anthropology of Reading, the considerations were founded on Turner and Bruner (1986), Larrosa (2019), Boyarin (1992), Zumthor (2020) and Schechner (2020), discussing with greater emphasis the concepts of experience and performance. In addition to the literature review, this research consisted of a descriptive study of the literary reading practices of the group mentioned, divided into two stages of data collection: in the first, in order to trace the reading profile, it was used an online questionnaire sent to 80 teachers, contacted via 4th CRE and BRAZ-TESOL, with the return of 55 instruments. In the second stage, 10 subjects who had responded to the questionnaire were chosen to be interviewed, aiming at revealing the performative reading experiences of each participant. Throughout this thesis, it is demonstrated that the profile of the English teacher-reader is characterized by teachers with a degree in Modern Languages, having less than 10 years of teaching experience, working mainly in language schools and who declare their proficiency in English at the C1 level, according to CEFR. These teachers are considered readers since they read at least 5 books a year and perform literary readings in English and Portuguese, having read the last text in English two months ago and in Portuguese a month ago (with reference to the period of data gathering). The English teacher-reader cultivates reading practices by commenting on books read with friends and colleagues, as well as selecting literary readings for other reasons unrelated to the profession, although one considers that elective readings expand the understanding of the world and of teaching activities. As in-depth comprehension of the reading experiences of this reader profile, it was noticed that there is a generation influenced by contemporary titles, even though classic literary works also make up the researched group's reading repertoire. Regarding English, data revealed that readings would be even more constant in this language if access to the original work were not yet so difficult, in financial terms. The collected data reported that there are no readers in the group who participate in reading clubs, as they prefer to choose their literary texts based on individual criteria. There was also a consensus on the idea that literary reading involves a gesture of rupture in routine and the opening of a time and space that are oblivious to everyday life. Also, sharing literary experiences was described as a way to create connections with other readers. Another relevant aspect concerns the paper book, as a cultural object, being preferred to virtual formats. When entering the performative experience of literary reading, it is understood that, as the reader incorporates it, being cognitively, emotionally and physiologically involved by the pleasure of the text, such experience reveals itself as performance. [resumo fornecido pelo autor]
A presente tese analisa as práticas de leitura literária dos professores de língua inglesa no intuito de compreendê-las como experiências performáticas. A fundamentação teórica baseia-se em um entendimento de leitura, a partir dos estudos de Leffa (1996), Kleiman (1995), Solé (1998), Silva (1997), Jouve (2002), Terra (2014), Britto (2015), Eco (1991) e Petit (2009; 2013; 2019). Conta ainda com aspectos da Estética da Recepção, a partir das contribuições de Jauss (1979; 1994) e Iser (1979; 1999); bem como da Indústria Cultural, com as discussões propostas especialmente por Adorno (1986; 2010). Elementos da Sociologia da Leitura foram agregados à tese pelo aporte de Bourdieu (1982; 1996) e Chartier (1994; 2001a, 2001b) e, pela via da Antropologia da Leitura, as considerações tomaram como base Turner e Bruner (1986), Larrosa (2019), Boyarin (1992), Zumthor (2020) e Schechner (2020), discutindo com maior ênfase os conceitos de experiência e de performance. Além da revisão bibliográfica, a pesquisa compôs-se por um estudo descritivo das práticas de leitura literária do grupo mencionado, sendo dividido em duas etapas de coleta de dados: na primeira, com vistas a traçar o perfil de leitura do grupo em foco, utilizou-se de um questionário online enviado a 80 professores, contatados via 4ª CRE e via BRAZ-TESOL, tendo o retorno de 55 instrumentos. Na segunda etapa, foram eleitos 10 sujeitos respondentes do questionário, os quais foram entrevistados no intuito de revelar suas experiências performáticas de leitura. Ao longo desta tese, demonstra-se que o perfil do professor-leitor de língua inglesa caracteriza-se por professores licenciados em Letras, com menos de 10 anos de experiência docente, que atuam em escolas de idiomas e declaram proficiência na língua inglesa em nível C1, conforme o CEFR. Esse professor considera-se leitor já que lê pelo menos 5 livros por ano e realiza leituras literárias em inglês e em português, tendo lido seu último texto em inglês há dois meses e em português há um mês (tendo como referência a data de coleta de dados). O professor-leitor de língua inglesa cultiva práticas de leitura comentando sobre os livros lidos com amigos e colegas, bem como seleciona obras literárias por outros motivos alheios à profissão, muito embora considere que as leituras eletivas ampliam o entendimento do mundo e de sua atuação docente. Como aprofundamento da compreensão das experiências de leitura desse perfil de leitores, percebeu-se que há uma geração influenciada por título contemporâneos, mesmo que obras clássicas também componham o repertório do grupo pesquisado. Em relação à língua inglesa, os dados revelaram que as leituras seriam ainda mais constantes se o acesso à obra original não fosse ainda tão difícil, em termos financeiros. Os dados coletados relataram que no grupo não há leitores que participam de clubes de leitura, já que preferem eleger seus textos literários a partir de critérios individuais. Também foi consenso a ideia de que a leitura literária envolve um gesto de ruptura na rotina e abertura de um tempo e um espaço alheios ao cotidiano. Ainda, o compartilhamento de experiências literárias foi descrito como forma de criar conexões com outros leitores. Outro aspecto relevante diz respeito ao livro físico, enquanto objeto cultural, sendo preferido aos formatos virtuais. Ao adentrar propriamente na experiência performática de leitura literária, compreende-se que, na medida em que o leitor a incorpora, envolvido cognitiva, emocional e fisiologicamente pelo prazer do texto, tal vivência se revela como performance. [resumo fornecido pelo autor]
Keywords: Leitura; Professores - Livros e leitura; Professores - Formação; Interesses na leitura; Língua inglesa; Prática de ensino; Reading; Teachers - Books and reading; Teachers, Training of; Reading interests; Student teaching